The Contributions of Al-Shatibi, Izzuddin ibn Abdul Salam and ibn Ashur on Maqasid Al-Shariah: An Exploration - Maidawa, Ibrahim; Kabir Umar, Fa'iza; Gokaru, Shuaibu Umar (Jurnal Usuluddin, 2024)
Maqasid al-Shariah is one of the unique disciplines of Islamic knowledge, particularly Islamic law. Maqasid al-Shariah is very important in understanding the true objectives of Islamic texts more comprehensively and accurately. Al-Shatibi, Izzuddin ibn Abdul Salam and ibn Ashur are among the leading figures who served as important references for contemporary Islamic law researchers. This paper explores brief biographies and contributions of these three important figures in Maqasid al-Shariah. The methodology adopted in this paper is qualitative research using library methods and the data were obtained from classical and contemporary sources of Islamic law. The findings reveal the lasting contributions of the three outstanding scholars of Maqasid al-Shariah. This paper, therefore, is likely to contribute immensely towards a new insight into the discipline of usul al-fiqh and understanding key important references and proper documentation in the field of Maqasid al-Shariah for contemporary researchers and students willing to specialize in the field.